Phenylephrine and the risk of atrial fibrillation in critically ill patients: a multi-centre study from eICU database - Huang, ZhiMing; Li, Weichao; Xie, WeiXian; xun-hu, Gu; Li, Heng (Frontiers in Pharmacology, 2025)
BackgroundVasopressors are vital for maintaining blood pressure in critically ill patients, though they carry risks like irregular heartbeats and impaired cardiac oxygen balance. Existing studies have not definitively proven that phenylephrine triggers new atrial fibrillation (AF).AimsThis study was designed to assess pharmacological associations between phenylephrine utilization and new AF occurrence risk.MethodsThis multicenter retrospective study analyzed eICU database records. Propensity score matching (PSM) balanced baseline confounders. Cox regression models (unadjusted/adjusted) assessed phenylephrine-AF associations.ResultsIn this cohort encompassing 51,294 critically ill adults (mean age 62.4 ± 16.6 years; 53.5% male), propensity score matching established comparable cohorts: 2,110 phenylephrine-exposed patients and 6,330 matched controls. The analysis revealed a clinically significant disparity in new AF incidence, with phenylephrine-exposed patients demonstrating a 10.5% event rate (282/2,673) versus 4.9% (2,395/48,621) in non-exposed counterparts (p < 0.001). Multivariable-adjusted Cox proportional hazards models identified a 29% elevated risk of new AF associated with phenylephrine administration (aHR, 1.29; 95%CI, 1.05–1.58). Notably, this association remained robust across multiple sensitivity analyses employing alternative matching methodologies and covariate adjustments.ConclusionThis evidence positions phenylephrine as a modifiable new AF risk factor in critical care, supporting risk-aware vasopressor selection through benefit-harm analysis.